Heavy metal content in annually-banded coral Porites lutea at windward and leeward of Tunda Island, Banten bay, West Java Indonesia. (January 2020) - Zamani, N P; Riska,; Prartono, T; Arman, A; Wahab, I
Abstract: Longterm fluctuation content of heavy metal concentrations (Sr, Cr, Fe, Zn, and Pb) was traced through the analysis of coral skeletal growth bands of massive coral core Porites lutea. Annual growth band was examined using X radiography. Heavy metal samples were extracted from each yearly layer of the core section. Seven samples of the coral skeleton were analyzed using neutron activation analysis and atomic absorption spectrometry to detect metal concentrations. The oldest layer of coring corals obtained from the windward side started from 1940, while in leeward of the island starting from 1969. All five metals from both sides were still detected until 2014. There was significant increase over time of the four metals (Cr, Fe, Zn. and Pb), while the concentrations of strontium remained relatively stable.